ANANLISIS POTENSI WISATA DENGAN METODE SMART BERDASARKAN PENDEKATAN COMMUNITY- BASED TOURISM - Sudarmanto; Edi Faizal (LPPM STMIK El Rahma Yogyakarta, 2019)
The application of the Smart Village concept involves many stakeholders and policies that accommodate all interests in the region. The development of tourist attractions in the village of Pleret is still not maximal because the priorities are not yet directed. This study will develop a computer-based system to support the analysis of priority tourism potential. The method of data collection uses questionnaires to obtain data sampling of several tourist objects. The analysis was carried out using the SMART method based on the criteria for the Community-Based Tourism approach. Based on the stages of the research that have been carried out and the results of system testing it can be concluded that, the developed system can be used to analyze tourism potential. The use of SMART method can determine the final result in the form of feasibility ranking based on the criteria value of an object. System testing shows that manual calculations and system calculations are the same, so that the system developed successfully and validly in analyzing input data and can be used as a tool to evaluate the potential of tourism objects.